The international security and the contemporary global threats (2010)
This paper analyzes security changes within the contemporary international system and the nature of the main state actors interacting in current conflicts. To achieve this goal, the text is divided into three parts: the first, in which the state is still viewed as the relevant actor of the international system; the second, where changes in the international context and the way they have affected the state are described. In the third part, based on the cold spell, a balance of the current perception models of global threats is shown.